1999
DOI: 10.1002/(sici)1098-2329(199922)18:2<125::aid-adv3>3.0.co;2-a
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing the joint strength of ultrasonically welded thermoplastics

Abstract: Ultrasonic welding of thermoplastics has become an important process in industry because of its relatively low cost and its high quality joints. However, the optimization of this technique has been essentially based on a trial‐and‐error process. In this report, an L18 experimental matrix design based on the Taguchi method was conducted to optimize the joint strength of ultrasonically welded thermoplastics. For the factors selected in the main experiments, weld time and amplitude of vibration were found to be t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(15 citation statements)
references
References 13 publications
0
15
0
Order By: Relevance
“…Typically, EDs are shaped like triangular, semi-circular or rectangular protrusions. [7][8][9][10][11][12][13] However, a simpler shape, so-called 'flat energy directors' , made of a neat polymer CONTACT Genevieve palardy g.palardy@tudelft.nl…”
Section: Introductionmentioning
confidence: 99%
“…Typically, EDs are shaped like triangular, semi-circular or rectangular protrusions. [7][8][9][10][11][12][13] However, a simpler shape, so-called 'flat energy directors' , made of a neat polymer CONTACT Genevieve palardy g.palardy@tudelft.nl…”
Section: Introductionmentioning
confidence: 99%
“…Semi-crystalline polymers such as HDPE, PP, PE, and polyester are generally difficult to weld ultrasonically due to the greater energy required to melt crystals and initiate intermolecular diffusion, and they are particularly difficult in the far-field configuration, due to damping. Liu et al ultrasonically welded amorphous polystyrene (PS) and semicrystalline PP [80]. They found that weld time and amplitude of vibration were significant parameters affecting weld strength.…”
Section: Friction Weldingmentioning
confidence: 99%
“…They modeled the viscoelastic heating of the ED assuming adiabatic heating and used elastic analysis to estimate the strain amplitude within parts. Liu et al 10 carried out optimizing studies of the joint strength of ultrasonically welded joints using statistical methods. The results of their study indicate that the weld time and the amplitude of vibration were the principal factors affecting the strength of the joint.…”
Section: Literature Reviewmentioning
confidence: 99%